2016
DOI: 10.1080/13573322.2016.1226792
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the relationship between pedagogy, technology and learning in health and physical education

Abstract: This paper seeks to address two key questions: 1) how could a pedagogically-driven approach to the use of DigiTech in HPE benefit young people's learning; and 2) what steps are required to develop new DigiTech pedagogies? The paper is a response to the largely pessimistic views presented in this journal by Gard, Lupton and Williamson about the role of technology in Health and physical Education (HPE). In this paper, we argue that while we need to be aware of the risks, we also need to explore the opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
146
0
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(173 citation statements)
references
References 45 publications
1
146
0
26
Order By: Relevance
“…In agreement with a substantial and international evidence-base, critical pedagogical approaches are required in schools to address the societal, narrow and normative discourses of health (Burrows & Wright, 2004;Casey et al, 2017;Gard, 2014;Harris et al, 2017;Powell & Fitzpatrick, 2015). The suitability of a critical approach rather than an exclusively physical activity promoting approach is further supported by the views of young people in this study.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In agreement with a substantial and international evidence-base, critical pedagogical approaches are required in schools to address the societal, narrow and normative discourses of health (Burrows & Wright, 2004;Casey et al, 2017;Gard, 2014;Harris et al, 2017;Powell & Fitzpatrick, 2015). The suitability of a critical approach rather than an exclusively physical activity promoting approach is further supported by the views of young people in this study.…”
Section: Discussionmentioning
confidence: 54%
“…In contrast to literature that advocates for the value of surveillance and the use of healthy lifestyle technologies in physical education contexts (Casey et al, 2017;Williamson, 2015), the young people stressed that there would be no educational value of integrating technology and that technology could negatively impact on their wellbeing. Yet, while a critical approach is commonly cited as way of supporting young people to navigate societal health discourses, evidence on the skills young people need to acquire, what a critical approach entails and how physical educators might practice a critical approach is more limited, particularly with regard to self-tracking and digital technologies (Casey et al, 2017;Powell & Fitzpatrick, 2015;Rich & Miah, 2017). Armour (2014) and Dudley, Goodyear, and Baxter (2016), as well as others, stress that the starting point for any pedagogical encounter should be the diagnosis of learners needs, understandings and skills.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…25,26 Yet the evidence base on the health-related impact of young people's (age [13][14] use of healthy lifestyle technologies is limited. 14,20,21 A recent systematic literature review on adolescents and young adults (age 12-25 years) identified only 2 empirical studies that measured the health-related effects of using nutritional or physical activity apps. 21 Further, the limited evidence base is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Given that young people are becoming increasingly tethered to their mobile devices, 18 alongside reports that they are increasingly turning to technology for health information, 19 healthy lifestyle technologies should be considered as tools to address physical inactivity in young people. 20,21 Though most empirical evidence on healthy lifestyle technologies is based on assessing quality and validity, 22 an emerging evidence base in young adults demonstrates that commercial wearable fitness trackers and their associated apps increase physical activity levels and impact motivational constructs of enjoyment, challenge, affiliation, and positive health motivation. 23 Young people (age [11][12] have also reported finding features of real-time feedback and competition from the commercial Fitbit motivating, 24 suggesting that promotion of self-monitoring and goal-setting behaviors can increase physical activity levels.…”
Section: Introductionmentioning
confidence: 99%